2015
DOI: 10.1186/s40249-015-0051-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the usefulness of integrated disease surveillance and response on suspected ebola cases in the Brong Ahafo Region, Ghana

Abstract: BackgroundThis study assessed the quality, core and support functions of the integrated disease surveillance and response (IDSR) system relating to 18 suspected cases of Ebola virus disease (EVD) in the Brong Ahafo Region, Ghana.MethodsData was collected on selected indicators of the surveillance system relating to 18 suspected cases of EVD, from epidemiological week 19 to 45 of 2014. We conducted in-depth interviews with seven medical directors and two district directors of health services, and also reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 6 publications
8
45
0
Order By: Relevance
“…Focused efforts to improve speci c surveillance functions in connection with PC-NTDs are paramount for effective identi cation of disease foci to inform targeted treatment and halt disease transmission. However, a review of existing literature identi ed unwavering focus on noti able diseases in assessing the performance of surveillance systems [41,[47][48][49][50][51][52]. Therefore, comparable ndings to the current study were based mostly on assessment of surveillance functions within the IDSR system with a leaning to noti able conditions.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Focused efforts to improve speci c surveillance functions in connection with PC-NTDs are paramount for effective identi cation of disease foci to inform targeted treatment and halt disease transmission. However, a review of existing literature identi ed unwavering focus on noti able diseases in assessing the performance of surveillance systems [41,[47][48][49][50][51][52]. Therefore, comparable ndings to the current study were based mostly on assessment of surveillance functions within the IDSR system with a leaning to noti able conditions.…”
Section: Discussionmentioning
confidence: 70%
“…The idea of an integrated disease surveillance and response framework was propositioned by WHO based on the sub-optimal performance of vertical surveillance systems characterised by unstandardised case de nitions, numerous reporting forms, limited laboratory capacity and inadequately trained human resource [40]. Optimal functioning and implementation of the IDSR system requires consolidation of all strategic components including effective communication, enhanced laboratory capacity, improved training and sustainable resource provision [41,42]. A recent assessment of the regional IDSR system implementation status in Africa indicated that most countries had implemented the IDSR framework [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although the effectiveness of surveillance systems for early EVD identification has been previously assessed , to our knowledge, this is the first study to examine the application of IDSR surveillance during EVD outbreaks, as well as to examine reporting trends of EVD differential diagnoses during EVD outbreaks. There are several limitations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…As supported in the study by Ndiaye et al (28), including CBS in existing projects can be important to both engage the communities, but also for sustainability and to ensure volunteers do not perceive it as a stand-alone project with other expectations and requirements than the regular volunteer programs. As in Sierra Leone, where there was a need for full coverage quickly, this is not always possible, but should be something to consider when planning implementation.…”
Section: Volunteer Work Combined With Paid Workmentioning
confidence: 96%
“…This should be considered according to context when implementing CBS. As with a study conducted in Niger, the community members received basic education to motivate them to notify health workers about possible cases in a timely matter [28]. Some of the CBVs also described alternative solutions to address the heavy workload, like organizing sub-groups of community members and agreements with community leaders to report rumors.…”
Section: Key Findingsmentioning
confidence: 99%